Intellectual property rights in the Internet: extraterritorial recognition or new conflict of law rules? - Leanovich, Elena B. (Journal of the Belarusian State University. International Relations, 2018)
The article is devoted to the new tendencies of application of mechanisms of private international law in intellectual property cases. The author explores conflict of law rules applicable to intellectual property relations, and shows the change of the traditional territorial approach to the disclosure of the legal content of intellectual property rights. The settlement mechanism for disputes arising from violations of intellectual property rights in domain names serves as the basis of the research. It is concluded that conflict of law rules on intellectual property demand new localization factors if corresponding relations take place in the Internet. The author proposes to adhere to the most flexible concept of the territorial nature of intellectual property rights in disputes on intellectual property settled by online procedures alternative to litigation in national courts.
Keywords: intellectual property; private international law; conflict of law rules; applicable law; territoriality; extraterritoriality; criterion of closest connection; domain names; trade marks